Biocompatible alkyne arms containing Schiff base fluorescence indicator for dual detection of CdII and PbII at physiological pH and its application to live cell imaging. Issue 13 (20th May 2020) - Jebastin Andrews, S. G.; Benita Jeba Silviya, S.; Jeyanthi, Dharmaraj; Sathya Devi, E.; Winfred Jebaraj, J.; Balakrishnan, Chithiraivel
Abstract : An alkyne arms containing salen-type Schiff base ligand L acts as a dual sensor for Cd II and Pb II with well-separated excitation and emission wavelengths. The ligand L has been utilized in cell imaging studies for both metal ions. Abstract : An alkyne arms containing salen-type Schiff base ligand, 6, 6′-((1 E, 1′ E )-(1, 2-phenylenebis(azanylylidene))bis(ethan-1-yl-1-ylidene))bis(3-(prop-2-yn-1-yloxy)phenol) (H2 L ), is reported here as a dual chemosensor for Cd II and Pb II ions. The ligand H2 L was characterized by various spectral methods. The ligand H2 L acts as a dual sensor for Cd II and Pb II in methanol/HEPES buffer (5 mM, pH 7.3; 1 : 9 v/v) at room temperature with well-separated excitation and emission wavelengths. The emission intensity at 553 nm of H2 L is shifted and a new band appeared at 578 nm with the increase in the presence of Cd II when it is excited at 420 nm. With excitation at 410 nm, the emission intensity of H2 L at 485 nm shifted and a new band appeared at 505 nm with the increase in the presence of Pb II . The quantum yield of H2 L increases considerably in the presence of Cd II and Pb II . The compound H2 L is non-fluorescent; however, in the presence of Cd II and Pb II, the compound H2 L is highly fluorescent with well-separated excitation and emission wavelengths, indicating that the metal ion is coordinated through phenolic oxygen and imine nitrogen of the Schiff base blocking the PET (Photoinduced Electron Transfer) process and stimulating the CHEF (Chelation Enhanced Fluorescence) process, to increase the fluorescence intensity of H2 L . The detection limit values of H2 L are in a nano-molar range for both metal ions, confirming very high sensitivity of H2 L . The L·M II binding mode and the recognition mechanism of the sensor were explored by Job's plot, 1 H NMR, FT-IR, pH and DFT calculations. Besides, H2 L was successfully utilized in cell imaging studies for both metal ions in MCF 7 cells.